Constructing 'Data Development Analysis' performance measures: a case study from the Greek Public Sector - Vasilakis, Athanasios G. (SPOUDAI Journal of Economics and Business, 2005)
Rapid changes in life-long training and performance measurement are posing serious questions to the work environment of public sector managers to undergo fundamental changes. Consequently, a Balanced Scorecard framework is attempted to increase the value of taxpayers' money and provide accountability of decision makers' contribution. A field research of 14 directors of Decision Making Units with their civil servants trained at the state training center of the Greek Ministry of Economy and Finance, constructs the 'Data Envelopment Analysis' via a modified Balance Scorecard (BSC). This paper illustrates empirical evidence on few selective key performance indicators, which finally measure the performance of public training programs JEL Classification: M49